'Green' coagulant application with activated carbon: dosing sequence and removal of selected micropollutants and effluent organic matter from municipal wastewater. Issue 8 (3rd April 2022) - Ivančev-Tumbas, Ivana; Bogunović, Minja; Vasić, Vesna; Šćiban, Marina; Tubić, Aleksandra; Leovac Maćerak, Anita; Prodanović, Jelena
ABSTRACT: Combination of 'green' coagulation and powdered activated carbon adsorption was tested for removal of benzophenone (BP), benzophenone-3 (BP-3) and caffeine (CF) from treated municipal wastewater at realistic concentration levels (1–2 µg/L). At the same time it was tracked how the process affected effluent organic matter (EfOM) by measuring chemical oxygen demand (COD). Green coagulant was produced from dry common bean seed in laboratory. Combined coagulation-adsorption experiments were performed by applying different dosing sequences of process materials. Removal of hydrophobic BP and BP-3 by separate adsorption (from 79 to 98%) was not significantly hindered by the addition of the coagulant (activated carbon dose of 5 or 20 mg/L). However, in some cases negative effects were observed for hydrophilic caffeine, depending on the carbon dose, dosing sequence and presence of total suspended solids (TSS). Thus, when coagulant was firstly added into water without TSS before low activated carbon dose of 5 mg/L, caffeine removal dropped from 26% to 5%. Conversely, when TSS were present in the water sample, the removal of caffeine was not hindered under the same PAC dose and dosing sequence. The importance of the process optimisation related to removal of organic micropollutans of different hydrophilicity has been shown in this paper. Removal of around 30% of COD regardless of the dosing sequence was achieved. GRAPHICAL ABSTRACT: UF0001